Career Re-Invention in the Post-Pandemic Era - Hai-Jew, Shalin (IGI Global, 2022)
Long before the COVID-19 pandemic, humanity was facing economic hardships with human jobs going to automation, AI, and machines. In the downward slope of the pandemic, large percentages of the world's population are without work, and many are still in isolation and social distancing for biosafety and health. If it is true that crisis brings out opportunities, then this is a highly opportune moment for humanity to redefine and move forward. Career Re-Invention in the Post-Pandemic Era explores how people in their respective localities are adapting for a new economy through new understandings of.